PEMBERDAYAAN REMAJA PUTRI DALAM PENINGKATAN KADAR HAEMOGLOBIN MELALUI PENGELOLAAN PUDING BUAH NAGA MERAH DAN PUDING BUAH BIT - Novy Ramini Harahap; Mila Syari; Raudah Raudah; Yulina Yulina; Korriati Manurung (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2023)
Anemia is still a problem that is often found in adolescents, especially in young women. Anemia can be caused by infectious diseases, inadequate intake of nutrients, loss of blood (menstruation) and knowledge. Adolescent girls are one of the groups that are prone to suffer from iron deficiency anemia because they have a high need for iron for growth. Iron is a mineral that is needed to form erythrocytes and also acts as a component to form myoglobin and functions in the body's defense system. Anemia can cause low learning achievement and can reduce the body's resistance so that it is susceptible to infection. Beetroot and red dragon fruit are easily obtained and consumed by teenagers. Beets and red dragon fruit contain anthocyanin flavonoids which are very useful in the formation of red blood cells (erythrocytes). The nutritional content of beets is folic acid, potassium, fiber, vitamin C, magnesium, tryptophan, iron, copper and phosphorus. The content of folic acid and iron in beets can be used as an option in treating anemia. Efforts are made in the form of giving dragon fruit pudding and beetroot pudding which are high in iron and vitamin C which are expected to increase iron levels in adolescents. Community service aims to increase youth knowledge about anemia and its treatment, as well as the use of food as an alternative treatment for anemia. The methods used were lectures, questions and answers, checking Hb levels, and giving dragon fruit and beetroot pudding. This community service was carried out for 30 young women, on January 16, 2023 at the Bima Utomo Batang Quiz Vocational School. North Sumatra. The output of this community service will be published in print and online media. Keywords: Anemia, Adolescents, Pudding, Red Dragon fruit, beets